Africa Transport Policies Performance Review : The Need for More Robust Transport Policies - Runji, Justin (World Bank, Washington, DC, 2015)
This working paper summarizes the key findings of the African Transport Policy Performance Review, carried out by SSATP in selected Anglophone and Francophone countries in 2013. It highlights the performance of transport policies focusing on the main transportation modes, excluding maritime and aviation, and is augmented by outcomes of related work carried out mainly by SSATP and the World Bank. The key objective is to convey the salient messages, and to point out the need for more transformational and pragmatic transport policy objectives and strategies, in an effort to enhance the efficiency and competitiveness of the sector. The paper addresses some fundamental policy issues, that affect transport performance in Sub-Saharan African countries and is intended for transport sector policy level decision-makers.